SISTEM INFORMASI UJIAN ONLINE SISWA PADA SMK UNWANUL FALAH BERBASIS INTERNET - MZ, Dedy Sofyan; Sunardi, Sunardi; Riana, Riana; Subli Ibrahim, Ahmad Rahmadi (JUTECH : Journal Education and Technology, 2024)
Exams are one way of assessing learning outcomes or measuring a person's ability level while participating in learning activities. Conditions like this are considered less effective because they have to add more questions, and the teacher must correct the students' answers individually. This research aims to create a website-based online exam information system using the MySQL database at Unwanul Falah Vocational School. The information-gathering technique used is observation, interviews and literature studies, while the development method is the waterfall method. This internet-based Online Examination Information System can be used to support online examinations. Apart from that, when taking online exams, students with faster exam results in terms of time do not need to use paper answer sheets so they can save costs, especially paper, stationery and others for schools and teachers do not need to correct answers because the answer results will be automatically displayed and finished the exam.